The miniJPAS survey - the role of group environment in quenching star formation - González Delgado, Rosa M.; Maturi, Matteo (Astronomy and astrophysics, 2022)
The miniJPAS survey has observed ∼1 deg 2 of the AEGIS field with 60 bands (spectral resolution of R ∼ 60) in order to demonstrate the scientific potential of the Javalambre-Physics of the Accelerating Universe Astrophysical Survey (J-PAS), which will map ∼8000 deg 2 of the northern sky over the coming years. In particular, this paper demonstrates the potential of J-PAS in detecting groups with mass of up to 1013 M ⊙ and in characterising their galaxy populations up to z ∼ 1. The parametric code BaySeAGal is used to derive the stellar population properties by fitting the J-PAS spectral energy distribution (SED) of the galaxy members in 80 groups at z ≤ 0.8 previously detected by the AMICO code, and of a galaxy field sample retrieved from the whole miniJPAS down to r < 22.75 (AB). Blue, red, quiescent, and transition (blue quiescent or green valley) galaxy populations are identified through their rest-frame (extinction-corrected) (u<i − r) int colour, galaxy stellar mass (M ⋆), and specific star formation rate (sSFR). We measure the abundance of these galaxies as a function of M * and environment in order to investigate the role that groups play in quenching star formation. Our findings are as follows. (i) The fraction of red and quiescent galaxies in groups increases with Mv⋆ and is always higher in groups (28% on average) than in the field (5%). (ii) The quenched fraction excess (QFE) in groups shows a strong dependence on Mv⋆, and increases from a few percent for galaxies with M⋆ < 10 10 M ⊙ to higher than 60% for galaxies with M ⋆ > 3 × 10 11 M ⊙. (iii) The abundance excess of transition galaxies in groups shows a modest dependence on M ⋆, being 5%-10% for galaxies with M ⋆ < 10 11 M ⊙. (iv) The fading timescale, defined as the time that galaxies in groups spend in the transition phase, is very short (< 1.5 Gyr), indicating that the star formation of galaxies in groups declines very rapidly. (v) The evolution of the galaxy quenching rate in groups shows a modest but significant evolution since z ∼ 0.8. This latter result is compatible with the expected evolution with constant QFE = 0.4, which has been previously measured for satellites in the nearby Universe, as traced by SDSS. Further, this evolution is consistent with a scenario where the low-mass star forming galaxies in clusters at z = 1-1.4 are environmentally quenched, as previously reported by other surveys.
Gesehen am 01.02.2023